Effectiveness of Using The Empty Outline Strategy With Cooperative Learning in Teaching Reading Skills - Nur Adzkia Kamilah; Shodiqin, Rahmat; El Sayid, Mohamed (Jurnal Al-Maqoyis, 2023)
To avoid becoming monotonous in the classroom, learning requires creativity and innovation. More and more new ideas are available for projects that support educational goals. For example, the education model, method, strategy and means. Therefore, the researcher is interested in studying the effectiveness of using the blank chart strategy in cooperative education in teaching reading skills to seventh grade students at the Islamic Brotherhood Middle School in Banjarmasin. The aim of this research was to determine the effectiveness of the blank chart strategy in cooperative learning in enhancing students' reading comprehension. Experimental and quantitative approaches are used in this research. The population in this research is seventh grade students and its sample is taken from the community collector. The design of this research used an experimental group and a control group. The experimental group was treated using the blank chart strategy in cooperative education, and the control group did not use it. The results showed that there was a difference between the pre- and post-test scores for each category, but there was no significant difference in the comparison between the experimental category and the control category. Based on the results of u-test calculation with IBM SPSS v.22 application, the Sig (2-tailed) value of 0.174 is greater than 0.05, then Ha is rejected and Ho is accepted. Therefore, the results of using the blank chart strategy in cooperative learning in teaching students' reading skills are ineffective.